2006
DOI: 10.1111/j.1540-4560.2006.00487.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity, Culture, and Child Maltreatment

Abstract: Increasingly, child maltreatment research has begun to address ethnicity and culture in both empirical studies and theoretical articles. Despite the expansion of these efforts, cross-cultural research in child maltreatment has raised more questions than it has answered; and it has highlighted the elusiveness of culture-specific constructs to scientific study. Research to date has been hampered by several challenges including the failure to disentangle ethnicity and culture. In this article, we provide a review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
71
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(74 citation statements)
references
References 71 publications
1
71
0
2
Order By: Relevance
“…[15][16][17][18] Indeed, considerable differences appear to exist between Asia and other regions in the frequency of child sexual abuse and intrafamilial or school-based physical abuse. [19][20][21][22] The factors that potentiate child abuse and place children at risk of poor mental health might not be generalizable across cultures. For example, some of the main risk factors for both child abuse and mental distress in children in economically developed nations, such as parental divorce, step-parenting, maternal alcohol and drug abuse and neighbourhood violence, 4,7 are comparatively rare in Asian countries.…”
Section: Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17][18] Indeed, considerable differences appear to exist between Asia and other regions in the frequency of child sexual abuse and intrafamilial or school-based physical abuse. [19][20][21][22] The factors that potentiate child abuse and place children at risk of poor mental health might not be generalizable across cultures. For example, some of the main risk factors for both child abuse and mental distress in children in economically developed nations, such as parental divorce, step-parenting, maternal alcohol and drug abuse and neighbourhood violence, 4,7 are comparatively rare in Asian countries.…”
Section: Researchmentioning
confidence: 99%
“…For example, some of the main risk factors for both child abuse and mental distress in children in economically developed nations, such as parental divorce, step-parenting, maternal alcohol and drug abuse and neighbourhood violence, 4,7 are comparatively rare in Asian countries. In addition, researchers in countries with multicultural populations, particularly in North America, often emphasize ethnic and cultural differences, 22,23 yet this source of variation may be less influential in comparatively monoracial societies, such as China, Japan and Viet Nam.…”
Section: Researchmentioning
confidence: 99%
“…Beyond pointing out cultural differences in prevalence rates, Elliott and Urquiza (2006) also reviewed cultural differences in potential mechanisms that might explain the differing child abuse rates. For example, researchers have long suggested that how one interprets differences in reports of sexual abuse by cultural groups should be informed by ethnic differences in willingness to disclose abuse as influenced by emphases on family and collectivistic beliefs, filial piety, and restraint in emotional expression.…”
Section: Environment and Social Network Factorsmentioning
confidence: 99%
“…Factors such as poverty may lead to heightened attention from state authorities and thereby disproportionately increase the number of cases reported among certain ethnic groups. Although research studies do point to variations in the child protective system's reporting of and response to reported child abuse from different cultural/ethnic backgrounds (Elliott & Urquiza, 2006), societal and familial factors (e.g., exposure to community violence, single-parent homes) continue to confound the issue. Therefore, whether ethnic differences in prevalence rates in childhood are due to actual higher incidence of abuse or reporting rates remains unclear.…”
Section: Environment and Social Network Factorsmentioning
confidence: 99%
“…In a secondary school survey in Malaysia, emotional and physical child abuse were the most common, and 22.1% had experienced more than one type of child abuse (Choo, Dunne, Marret, Fleming, & Wong, 2011). The prevalence of child abuse, including CCSA, may differ between countries in Asia (Chen et al, 2006;Elliott & Urquiza, 2006). For example, the prevalence of CCSA appears to be lower in studies conducted in Asian countries, compared with non-Asian samples (Elliott & Urquiza, 2006), which might be attributed to greater conservative cultural sexual norms and restraint in emotional expression in Asia (Elliott & Urquiza, 2006).…”
mentioning
confidence: 99%